Mentor’s Perception of the Future Science Teacher’s Teaching Practice - Radulović, Branka; Jovanović, Tamara; Gadušová, Zdenka; Hašková, Alena; Pavera, Libor (Journal of Education Culture and Society, 2022)
Aim. The paper presents feedback on the effects of a new approach to the teaching practice of teacher trainees introduced in Serbia. Verification of the new approach is connected with a mentor training conception which has been under preparation within the frame of Erasmus+ project 2020-1-SK01-KA201-07825 Mentor training addressed in mutual cooperation of higher education institutions from Slovakia, Czech Republic, Hungary, and the Republic of Serbia.Methods. Within the frame of the new approach, verification structured interviews were carried out with a research sample of ten mentor teachers—science teachers from primary and secondary schools. The teachers were asked about the teacher trainees’ knowledge and skills (competences) they use within the lessons taught by them during their teaching practice, ways to improve the mentoring process, as well as mentors’ competences and the ability to self-assess.  Results. The researchers collected rather positive opinions of mentors about mentees’ knowledge and skills they come to schools with. At the same time, the mentors expressed high satisfaction with their own knowledge about their mentoring role and competences.Conclusion. The paper presents, on the one hand, a good example of synergy of the national school policy strategies, introducing new approaches to the teaching practice of teacher trainees in Serbia. On the other hand, the goals of an international project are presented, which are meant to improve the quality of mentor-teachers at schools in Serbia.